Aesthetics and subjectivity - Bowie, Andrew (Manchester University Press, 2003)
This new, completely revised and re-written edition of aesthetics and subjectivity brings up to date the original book's account of the path of German philosophy from Kant, via Fichte and Holderlin, the early Romantis, Schelling, Hegel, Schleimacher, to Nietzsche, in view of recent historical research and contemporary arguments in philosophy and theory in the humanities. The original book helped make subjectivity, aesthetics, music and language a significant part of debate in the humanity. Bowie develops the approaches to these areas in relation to new theoretical advances which bridge the divide between the continental and analytical traditions of philosophy. In light of the huge growth of interest in German philosophy as a resource for re-thinking both literary and cultural theory, and contemporary philosophy, aesthetics and subjectivity will be indispensable reading for students and teachers in all humanities subjects, from literature, to philosophy, to music and beyond.